The aspect of vector control using the asynchronous traction motor in locomotives - Liudvinavičius, Lionginas; Lingaitis, Leonas P.; Dailydka, Stasys; Jastremskas, Virgilijus (Transport, 2009)
The article examines curves controlling asynchronous traction motors increasingly used in locomotive electric drives the main task of which is to create a tractive effort‐speed curve of an ideal locomotive Fk = f(v), including a hyperbolic area the curve of which will create conditions showing that energy created by the diesel engine of diesel locomotives (electric locomotives and in case of electric trains, electricity taken from the contact network) over the entire range of locomotive speed is turned into efficient work. Mechanical power on wheel sets is constant Pk = Fkv = const, the power of the diesel engine is fully used over the entire range of locomotive speed. Tractive effort‐speed curve Fk(v) shows the dependency of locomotive traction power Fk on movement speed v. The article presents theoretical and practical aspects relevant to creating the structure of locomotive electric drive and selecting optimal control that is especially relevant to creating the structure of locomotive electric drive using ATM (asynchronous traction motor) that gains special popularity in traction rolling stock replacing DC traction motors having low reliability. __e frequency modes of asynchronous motor speed regulation are examined. To control ATM, the authors suggest the method of vector control presenting the structural schemes of a locomotive with ATM and control algorithm. First published online: 27 Oct 2010